2018
DOI: 10.2337/db18-98-lb
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome Assessment of the Effectiveness of Insulin Degludec (Degludec) in Real-life Medical Practice (CONFIRM)—A Comparative Effectiveness Study of Degludec and Insulin Glargine 300U/mL (Glargine U300) in Insulin-Naïve Patients with Type 2 Diabetes (T2D)

Abstract: The CONFIRM study compared the real-world effectiveness of degludec and glargine U300 in insulin-naïve patients with T2D. This retrospective, non-interventional comparative effectiveness study used electronic health records of U.S.-based patients from Explorys, with propensity-score matching to balance baseline characteristics between cohorts. The primary endpoint, ∆A1C from baseline to 6 months follow-up, was estimated using a repeated-measure analysis with subject as random effect. Rate of hypoglycemic episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
11
1
1
Order By: Relevance
“…Finally, it is worth noting that the CONFIRM population appears to have a pattern of baseline medication that is inconsistent with what might be expected for an insulin‐naïve cohort. Initial insulin doses, among those patients with data available, appear to be much higher than would be expected (given their body weight), at around 40 units/d . This contrasts with the ~20 units/d in the present study, and the doses in the BRIGHT trial, which followed the products' licenses (Gla‐300: 0.2 units/kg 2 IDeg: 10 units 3 ).…”
Section: Discussioncontrasting
confidence: 82%
“…Finally, it is worth noting that the CONFIRM population appears to have a pattern of baseline medication that is inconsistent with what might be expected for an insulin‐naïve cohort. Initial insulin doses, among those patients with data available, appear to be much higher than would be expected (given their body weight), at around 40 units/d . This contrasts with the ~20 units/d in the present study, and the doses in the BRIGHT trial, which followed the products' licenses (Gla‐300: 0.2 units/kg 2 IDeg: 10 units 3 ).…”
Section: Discussioncontrasting
confidence: 82%
“…database. 36 The analysis found significantly greater HbA 1c reductions, Hence, the populations used for analysis were not necessarily well matched. In addition, the greater reduction of hypoglycaemia risk with IDeg compared with Gla-300 seen in CONFIRM could be explained by the higher rates of hypoglycaemia observed at baseline in the IDeg group, while rates of hypoglycaemia at follow-up were similar.…”
Section: Confirmmentioning
confidence: 93%
“…The effectiveness and safety of Gla‐100 or IDeg have been investigated in observational retrospective studies of such databases, such as the DELIVER and ReFLECT studies . Additionally, the LIGHTNING and CONFIRM trials compared rates of hypoglycaemia between Gla‐300 and IDeg reported in real‐world data from electronic healthcare records …”
Section: Hypoglycaemia Assessment In Rwe Studiesmentioning
confidence: 99%
“…86 Additionally, the LIGHTNING and CONFIRM trials compared rates of hypoglycaemia between Gla-300 and IDeg reported in real-world data from electronic healthcare records. 87,88 Given the less stringent protocols that are often associated with RWE studies, the diversity in hypoglycaemia reporting in these studies is likely to be even greater than that in RCTs. Hypoglycaemia docu- Furthermore, given that many observational studies are less resourceintensive, the capacity for long periods of follow-up is much greater than that for many RCTs.…”
Section: Rcts Versus Real-life Clinical Practicementioning
confidence: 99%